2022
DOI: 10.1039/d1sm01229k
|View full text |Cite
|
Sign up to set email alerts
|

An embedded interface regulates the underwater actuation of solvent-responsive soft grippers

Abstract: In this work, we report the role of an embedded interface between two polymer thin films in determining the overall folding and actuation characteristics of a bilayer system applied for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The tendency of the film to bend in a specific direction is determined by the rate of concentration change at a particular time. 65 ̆̆, the film does not experience any bending and remains as it is. It is observed in Figure 9b that the relative rate of concentration change is highest in the bottom layer, followed by the middle and top layer during the initial time of folding (up to ∼12 s).…”
Section: Case I: Actuation Under Immersed Environmentmentioning
confidence: 98%
“…The tendency of the film to bend in a specific direction is determined by the rate of concentration change at a particular time. 65 ̆̆, the film does not experience any bending and remains as it is. It is observed in Figure 9b that the relative rate of concentration change is highest in the bottom layer, followed by the middle and top layer during the initial time of folding (up to ∼12 s).…”
Section: Case I: Actuation Under Immersed Environmentmentioning
confidence: 98%
“…Furthermore, the unit cell and the passive layer are assumed to be made of the same material. A concern when it comes to bonding of layers with differing thermal coefficients is the separation of the layers, however, recent studies [73][74][75] have shown that strong interface adhesion can be achieved through appropriate interface engineering. The geometric and material properties of the proposed unit cell are as defined in table 1.…”
Section: Validation Of the Analytical Modelmentioning
confidence: 99%
“…The external stimulus is applied as a temperature field to the model in order to induce an eigenstrain. The materials and stimuli have been chosen such that the effective response mimics the behavior of the film proposed in Meena et al [73]. Boundary conditions are applied, constraining the left surface of the unit cell in the X direction and a point on the surface in the Y and Z directions to prevent rigid body motions.…”
Section: Validation Of the Analytical Modelmentioning
confidence: 99%
“…Motions previously achieved using motors and mechanical actuators are replaced by smart actuators that respond to specific stimuli 6–9 . Stimuli‐responsive actuators like light/heat‐responsive liquid crystal polymers, solvent/vapor‐responsive hydrogels and heat‐responsive shape memory alloys were recently developed 4,5,10–25 . Inspired by nature, researchers have developed actuators that can perform complex actions using these responsive systems.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Stimuli-responsive actuators like light/heatresponsive liquid crystal polymers, solvent/vapor-responsive hydrogels and heat-responsive shape memory alloys were recently developed. 4,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Inspired by nature, researchers have developed actuators that can perform complex actions using these responsive systems. Actuators which mimick the blooming of flowers, [26][27][28][29][30] motion of caterpillars, [31][32][33] trapping of flies like Venus flytrap 6 and tight rolling of proboscis of butterfly, 34,35 among others, were developed.…”
Section: Introductionmentioning
confidence: 99%